Emerging the regional innovation system in Vietnam: Case study of the area of Da Lat safe vegestables - Mai, Nguyen Phuong; Hung, Nguyen Vo (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
Practice in Vietnam shows that technological innovation in agriculture is not only undertaken in the form of knowledge transfer from S&T institutions to producers, but it also takes place in many other ways, especially through interactive learning between producers and different entities in the process of market exploration. In other words, innovation is not implemented in isolation but through the interaction of entities and institutions in the innovation system. Studies highlighted that regional innovation system (RIS) naturally formed in developing countries was the original foundation for the process of shaping and development of the national innovation system. With producers operating in the same industry concentrated on a long tradition region, the appearance of individuals with start-up entrepreneurship, and the presence of many supporting organizations and institutions, it has made Da Lat and its surroundings become a distinct region and possess a RIS on agricultural production. This paper analyzes the safe vegetable industry of Da Lat where innovation derives from learning based market interactions. This case study serves as an argument to the above statement. Code: 14061201